Climate change action as a project of identity: Eight meta-analyses. (September 2021) - Vesely, Stepan; Masson, Torsten; Chokrai, Parissa; Becker, Anna M.; Fritsche, Immo; Klöckner, Christian A.; Tiberio, Lorenza; Carrus, Giuseppe; Panno, Angelo
Highlights: Comprehensive meta-analysis of the links between identity and environmentalism. Environmental self-identity is strongly associated with environmentalism. Connectedness to nature is moderately to strongly linked to environmentalism. Place identity is only relatively modestly associated with environmentalism. Some social identities are moderately to strongly linked to environmentalism. Abstract: Identity can improve our understanding of personal climate action, particularly when climate action becomes an expression of a person's self. However, it is unclear which kind of self or identity is most relevant. Building on a comprehensive series of eight meta-analyses (using data from 188 published articles, N  = 414, 282 participants) this research systematically compares how strongly climate-friendly intentions and behaviors are associated with place identity, personal connectedness to nature, environmental self-identity (i.e., personal self-definition as a pro-environmentally acting person), and social identity (i.e., identification with social groups). Results suggest robust, medium-sized to strong links of both pro-environmental intentions and behaviors to people's nature connectedness ( r  = 0.44/0.52), environmental self-identity ( r  = 0.62/0.56), and identification with groups considered to support climate-friendly behavior ( r  = 0.48/0.51), but markedly weaker effects for identification with groups which are unrelated to environmental topics ( r  = 0.30/0.15) and for place identity ( r  = 0.18/0.32). Implications for policy interventions and psychological theory are discussed.